2011
DOI: 10.1186/1742-6405-8-30
|View full text |Cite
|
Sign up to set email alerts
|

Chronic alcohol ingestion exacerbates skeletal muscle myopathy in HIV-1 transgenic rats

Abstract: BackgroundSeparately, chronic alcohol ingestion and HIV-1 infection are associated with severe skeletal muscle derangements, including atrophy and wasting, weakness, and fatigue. One prospective cohort study reported that 41% of HIV-infected patients met the criteria for alcoholism, however; few reports exist on the co-morbid effects of these two disease processes on skeletal muscle homeostasis. Thus, we analyzed the atrophic effects of chronic alcohol ingestion in HIV-1 transgenic rats and identified alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 47 publications
2
20
0
1
Order By: Relevance
“…Moreover, we have demonstrated a strong association between the development of SAIDS wasting and decreased time to end-stage disease (from ~900 days in sucrose-fed SIV-infected to 390 days in chronic alcohol-fed SIV-infected macaques) [20]. Similar accentuation of muscle atrophy has been reported in chronic alcohol-fed HIV-1 transgenic rats [50, 51]. …”
Section: Alcohol and The Musculoskeletal System In Hivsupporting
confidence: 54%
See 1 more Smart Citation
“…Moreover, we have demonstrated a strong association between the development of SAIDS wasting and decreased time to end-stage disease (from ~900 days in sucrose-fed SIV-infected to 390 days in chronic alcohol-fed SIV-infected macaques) [20]. Similar accentuation of muscle atrophy has been reported in chronic alcohol-fed HIV-1 transgenic rats [50, 51]. …”
Section: Alcohol and The Musculoskeletal System In Hivsupporting
confidence: 54%
“…Similar derangements in growth factors and proinflammatory cytokine expression have been associated with wasting in AIDS patients [74, 75], as well as in other animal models of chronic alcohol feeding and HIV infection [51, 76, 77]. Proinflammatory cytokines including IL-6 and TNF-α have been determined to exert anti-insulin effects in both skeletal muscle and adipose tissue [78, 79].…”
Section: Alcohol and The Musculoskeletal System In Hivmentioning
confidence: 86%
“…Excess production of proinflammatory cytokines can decrease muscle protein synthesis (24), and an increase in muscle TNF-␣ and IL-6 mRNA is observed in some (8,66) but not other studies (62) in response to chronic alcohol feeding. Our current data confirm alcohol-fed rats have a selective increase in TNF-␣ and IL-6 mRNA in gastrocnemius, but no detectable change in IL-1␤ or NOS2.…”
Section: R892 Aging Alcohol and Muscle Protein Balancementioning
confidence: 95%
“…In addition to behavioral changes, Clary et al (2011) found that, in HIV-1Tg rats, chronic alcohol consumption accentuates skeletal muscle atrophy and decreases expression of anabolic factors, CT-1 and CNTF, indicaing that alterations in these signaling mechanisms may be involved in the loss of muscle mass associated with alcoholism, especially in HIV-infected populations (Clary, Guidot et al 2011). …”
Section: Behavioral Alterations In the Hiv-1tg Ratmentioning
confidence: 99%